Contribuição ao controle de inversores PWM alimentados em tensão conectados à rede através de filtro-LCL - Gabe, Ivan Jorge (2008)
This dissertation deals with the design of a robust current control loop applied to voltage source inverters connected to the grid thought LCL-filter used in distributed generation systems. The utilization of the LCL-filter bring the need of damping the characteristic resonance of the filter. Two alternatives are generally considered in the literature. The passive damping, that add a passive element, generally a resistor or a additional passive element in the filter circuit and the active damping, that introduce a specific controller in the inverter current control loop. The active damping present more flexibility in the implementation and do not present energy losses like passive damping, so is the preferred damping method in high power applications. The main challenge to the damping method is keep the performance and avoid instability and controllers interactions even when impedance variations occur in the grid. In this dissertation, are proposed two control schemes for achieve the active damping of the filter resonance. In the first one, a robust partial state feedback is derived to allocate the poles of the LCL-filter inside the unity ratio circle for a given grid impedance variation. The feedback gains are obtained by a LMI condition that assure robust pole location in a pre-establish region of the unity ratio circle. In the second method, is proposed a predictive state estimator based on the multirate observers theory. This estimator allow feeding back the estimated stated by the measure of only one state variable. Moreover, the predictive action of the observer, eliminate the time delay of the control loop improving the stability margins of the system. Experimental results of a setup of 10kW DSP based are presented.